The effect of metformin on mortality and severity in COVID-19 patients with diabetes mellitus. (August 2021) - Yang, Wenxing; Sun, Xuehong; Zhang, Jun; Zhang, Kui
Abstract: Aim: COVID-19 has spread globally with heavy impact on most countries and our therapeutic strategies in COVID-19 patients with diabetes are still limited. Recently, some new information was added to this field. We performed this updated meta -analysis to reveal the underlying effect of metformin on COVID-19 patients with diabetes. Methods: We searched the PubMed, Embase and CNKI (China National Knowledge Infrastructure) databases for all articles. The odds ratio (OR) corresponding to the 95% confidence interval (95% CI) was used to assess the effect of metformin on COVID-19 patients with diabetes. The statistical heterogeneity among studies was assessed with the Q-test and I 2 statistics. Results: We collected 17 studies including 20, 719 COVID-19 patients with diabetes. Our results found that metformin was associated with significantly decreased mortality and severity in COVID-19 patients with diabetes (OR = 0.64, 95% CI = 0.51–0.79 for mortality, and OR = 0.81, 95% CI = 0.66–0.99 for severity). Conclusions: Our meta -analysis indicated that following metformin treatment might benefit the patients with T2DM, both the mortality and severity. However, patients with severe COVID-19 should be monitored closely for the development of lactic acidosis, acidosis, and decreased kidney function.